Herpesvirus reactivation is associated with mortality in critically ill ICU patients with COVID-19: Insights from a retrospective single-center analysis of 455 cases - Stefanie Michel; Cilian Kempf; Nina Pirschtat; Frank Herbstreit; Bettina Budeus; Sebastian Voigt; Jutta Dedy; Thorsten Brenner; Simon Dubler (PLoS ONE, 2026)
Background Critically ill patients with COVID-19 frequently develop viral reactivation, yet the clinical significance of herpes simplex virus type 1 (HSV-1) and cytomegalovirus (CMV) remains a matter of debate. Methods We conducted a retrospective single-center study of 455 consecutive intensive care unit (ICU) patients with confirmed SARS-CoV-2 infection between March 2020 and December 2021. Patients underwent screening for HSV-1 and CMV in whole blood and respiratory samples. A multivariable model was used to independently investigate risk factors associated with mortality. Results The mean age was 57 years (range: 13–94 years), and 316 (69%) were male. During a median ICU stay of 14 (0–90) days, viral reactivation (either HSV-1 or CMV or both) occurred in 164 (36%) patients. HSV-1 and CMV co-reactivation was detected in 57 (13%) patients, isolated HSV-1 reactivation was observed in 54 (12%) patients and isolated CMV reactivation in 53 (12%) patients. Median time from ICU admission to viral detection was 4 days, with a stepwise increase with longer ICU stay. Detection of HSV-1 was associated with decreased ICU survival (32% versus 67%; p < 0.001) which remained significant after multivariable adjustment. Detection of HSV-1 but not CMV was associated with an increased need for invasive mechanical ventilation, veno-venous extracorporeal membrane oxygenation therapy, and the need for renal replacement therapy. Higher neutrophil-lymphocyte ratios were independently associated with an increased risk of ICU mortality and correlated with detection of HSV-1 and CMV. Conclusion Herpesvirus reactivation was common in critically ill patients with COVID-19. HSV-1 reactivation was associated with a more severe course of disease and increased ICU mortality.